Manfaat Pemberian Stik Gembili Untuk Menambah Berat Badan Anak - Maya Septriana; Myrna Adiyanti; Rini Hamsidi; Dwi Indah; Galuh Puja; Onny Priskila (Politeknik Negeri Jember, 2022)
50-60% parents reported that their child had feeding problems. One of the specific nutritional interventions by giving functional foods such as Gembili (Dioscorea esculenta L.). Gembili stick intervention in toddlers was using experimental quantitative research design and data collection methods with